A Review on Attachment and Adolescent Substance Abuse: Empirical Evidence and Implications for Prevention and Treatment. Issue 3 (July 2015) - Schindler, Andreas; Bröning, Sonja
Background: This paper reviews research on the relation of attachment and substance use disorders (SUD) in adolescence. Based on a theoretical introduction, we review evidence for a possible general link between SUD and insecure attachment, for links between specific forms of SUD and specific patterns of attachment, and for studies on family patterns of attachment in adolescence. Methods: Using medical and psychological databases, we identified 10 studies on adolescent SUD and another 13 studies on adult SUD. Results: Empirical evidence strongly supports the assumption of insecure attachment in SUD samples. With regard to specific patterns of attachment, results mainly point towards fearful and dismissing-avoidance, whereas single studies report preoccupied and unresolved patterns. Results indicate different patterns of attachment in different groups of substance abusers, that is, fearful-avoidant attachment in heroin addicts and more heterogeneous results in abusers of other substances. Explorative data suggest different types of insecure family attachment patterns, which might imply different functions of substance abuse and lead to different treatment recommendations. Methodological problems such as poor assessment of SUD and the use of different measures of attachment limit comparability. Conclusions: Although a lot of research is still needed to address the unknowns in the relation between attachment and SUD, there is strong evidence for a general link between SUD and insecure attachment. Data on connections between different patterns of attachment and different pathways towards SUD are less conclusive but mainly point to disorganized and externalizing pathways. Evidence suggests that fostering attachment security might improve the outcome of state-of-the-art approaches in both early interventional treatment and prevention. Implications for individual and family approaches are outlined.